Wan Lis, Fulap Stori : Leasing on Epi Island, Vanuatu - Porter, Raewyn (World Bank, Washington, DC, 2017)
This study of 23 leases over land on the island of Epi is the first of the Jastis Blong Evriwan (JBE) research activities to examine land and natural resource management (L&NRM) and access to justice on particular Vanuatu islands. The research will be repeated on the island of Tanna. To inform the broader context of land leasing in Vanuatu, JBE, in collaboration with the government of Vanuatu, has begun collecting and analyzing government land-leasing data. This process commenced in late 2009 and will ultimately make it possible for leasing patterns in each of the island studies to be placed in a broader national land-leasing context. The JBE Project Framework Document (PFD) for Vanuatu outlines a number of priority research areas in Land and Natural Resource Management (L&NRM) and Access to Justice. The research undertaken on Epi Island during March 2010 investigated the way customary groups negotiate and engage in land-lease dealings and the type and effectiveness of mechanisms and strategies people used to resolve disputes. This approach combined the L&NRM and access to justice research areas in order to: (i) document ways in which customary groups engage with the formal system; and (ii) increase understanding of the type of justice problems citizens face and the mechanisms and strategies people use to enforce their rights. Integrating these two research interests supported a more holistic understanding of the ways in which custom landholder groups operate in the context of legal pluralism.